Ethanolic Extracts of Shallot Leaves (Allium ascalonicum L.) as Botanical Pesticide for Controlling Fall Armyworms (Spodoptera fugiperda J.E. Smith) - Putri, Diah Asta; Nur Aini, Pradipta (Universitas Ahmad Dahlan, 2021)
The application of botanical pesticide is a positive long term approach to control S. frugiperda. Shallot leaves contain acetogenin compound, hence it has the potential to become botanical pesticide. This study is aimed at finding out the effects of ethanolic extract of shallot leaves on S. frugiperda larvae in vitro. Extract is prepared using maceration method with ethanol solvent. The method of treatment is Leaf Dipping. The study applies Completely Randomized Design with concentration of shallot leaf extract as treatment at 0 ppm, 250 ppm, 500 ppm, 750 ppm dan 1000 ppm. Each treatment consists of four repetitions. Examination is conducted for 24 hours. Examination parameter is mortality of larvae and LC50. Data are analyzed with One Way ANOVA (proceeded with LSD) and Probit analysis. The results suggest that shallot leaf extract at the concentration of 1000 ppm appears to be the most effective on the mortality of larvae. The obtained LC50 value is 263,02 ppm. The study indicates that shallot leaf extract can be applied as an alternative synthetic insecticide to control ini S. frugiperda.